COMPARATIVE EFFECTIVENESS OF A LOCALLY ADAPTED SALINE-BASED DEL NIDO CARDIOPLEGIA IN PEDIATRIC SEPTAL DEFECT REPAIR - Khodjiyev B.F., Satvaldiera E.A., Kuralov E.T., Abdukadirov A.A., Bayjumanov A.P., Jalilov G.M., Urinhujayev T.M., (Central Asian Journal of Medicine, 2025)
Background: In pediatric cardiac surgery, the prevention of ischemic myocardial injury remains a key factor in ensuring favorable outcomes. The cardioplegia technique selected during surgery plays a decisive role in protecting the immature myocardium in infants and toddlers undergoing correction of congenital heart defects (CHDs). Aim: To evaluate and compare the incidence of early postoperative myocardial injury in children aged 12 to 36 months who underwent open surgical repair of septal congenital heart defects, depending on the type of cardioplegic solution applied-crystalloid versus a locally adapted blood-based del Nido cardioplegia. Study Design and Methods: This single-center, prospective, comparative clinical study was carried out at the National Children's Medical Center (Uzbekistan) from February 2021 to December 2024. Ninety-one pediatric patients with atrial or ventricular septal defects were assigned to two treatment arms: 44 children received traditional cold crystalloid cardioplegia, while 57 were treated using a modified del Nido solution containing oxygenated blood in a 4:1 ratio. The main outcome measure was a persistent >10-fold elevation in plasma troponin I within 6 hours postoperatively and at the 24-hour mark. Additional parameters included left ventricular ejection fraction (LVEF) changes and need for inotropic support. Findings: The rate of significant troponin I elevation was considerably lower in the del Nido group (31.3%) than in the crystalloid group (62.5%; p < 0.001). Although both groups demonstrated a postoperative decline in LVEF, the reduction was markedly less in the del Nido group (18% vs. 30.7%), suggesting more efficient myocardial protection. Conclusions: The use of a blood-enhanced del Nido cardioplegia formulation demonstrated clear clinical advantages over crystalloid cardioplegia in pediatric patients undergoing septal defect repair, resulting in reduced biochemical markers of myocardial injury and better preservation of ventricular contractility in the early postoperative period.